2011
DOI: 10.1371/journal.pntd.0001187
|View full text |Cite
|
Sign up to set email alerts
|

Health Services for Buruli Ulcer Control: Lessons from a Field Study in Ghana

Abstract: BackgroundBuruli ulcer (BU), caused by Mycobacterium ulcerans infection, is a debilitating disease of the skin and underlying tissue. The first phase of a BU prevention and treatment programme (BUPaT) was initiated from 2005–2008, in the Ga-West and Ga-South municipalities in Ghana to increase access to BU treatment and to improve early case detection and case management. This paper assesses achievements of the BUPaT programme and lessons learnt. It also considers the impact of the programme on broader interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 18 publications
2
60
0
1
Order By: Relevance
“…This paper on the other hand focused on identifying social and economic factors that are considered when the affected and infected are making health seeking decisions on where and when to seek for health. About a third (35%) of the study participants was classified as having category three ulcers and this confirmed the proportionally high prevalence of severe ulcers in the study area compared to other endemic districts in Ghana (Ahorlu et al, 2013;Ackumey et al, 2011). The finding that decisions to seek health from health facilities are being influenced mainly by health workers, and/or family members rather than financial considerations contradict what was reported by Stienstra and colleagues that financial consideration was a reason for delay treatment seeking among BU patients (Stienstra et al, 2002).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This paper on the other hand focused on identifying social and economic factors that are considered when the affected and infected are making health seeking decisions on where and when to seek for health. About a third (35%) of the study participants was classified as having category three ulcers and this confirmed the proportionally high prevalence of severe ulcers in the study area compared to other endemic districts in Ghana (Ahorlu et al, 2013;Ackumey et al, 2011). The finding that decisions to seek health from health facilities are being influenced mainly by health workers, and/or family members rather than financial considerations contradict what was reported by Stienstra and colleagues that financial consideration was a reason for delay treatment seeking among BU patients (Stienstra et al, 2002).…”
Section: Discussionsupporting
confidence: 71%
“…Also, Ahorlu and colleagues have aptly demonstrated that it is essential to remove impediments that limit access to early effective treatment by implementing social interventions such as the provision of transportation to and from treatment centres on daily basis. It has been further established that early case detection is enhanced by organizing community outreach and screening activities in endemic villages (Ahorlu et al, 2013;Ackumey et al, 2011). Despite all these efforts, many patients still report late for diagnosis and treatment with severe ulcers coupled with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Findings, particularly narratives, indicate a genuine difficulty in diagnosing some pre-ulcer conditions, which is consistent with prior research findings. 15 Perceptions of the imminent severity or progression of Buruli ulcer have been identified as a contributing factor for delay in seeking medical treatment. 7,17 Buruli ulcer is known to affect poor, rural communities.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research in our study municipalities showed the importance of community-based surveillance activities from CSBVs and health professionals to detect early cases, increase awareness of Buruli ulcer, and availability and effectiveness of WHOrecommended antibiotic treatment. 15 Community-based surveillance has been used successfully for early case detection and in the management of Buruli ulcer in the study municipalities 15 and for Guinea worm eradication programs. 26 The presence of herbalists in the family (fathers, grandfathers, and uncles) and other itinerant herbalists made herbal treatment readily available and influenced respondent's choice of herbal treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation